MODEL PENYELESAIAN ALTERNATIF PERKARA PIDANA DALAM HUKUM ISLAM DAN RELEVANSINYA DENGAN PEMBAHARUAN HUKUM PIDANA INDONESIA - Yusuf, Hambali; Basri, Saifullah (Legality : Jurnal Ilmiah Hukum, 2018)
Many criminal cases that are not resolved either at the level of appeal or cassation level is an indication that there are problems in law enforcement. Islamic Criminal Justice provides much alternative settlement of criminal cases by maintaining a balance of the interests of the victim, the community, the State and the offender. This research aims to analyze the model, explain the alternative settlement of criminal cases in the Islamic law; how setting the model settlement of criminal cases in the Islamic law can be used as a model settlement of criminal cases in the criminal law of Indonesia, to find a model settlement of criminal cases in the Islamic law of relevance to criminal law updates Indonesia.    This research got that setting jarimah qishas-diyat placed as a kind of private law as rights adami. Setting model jarimah-diyat can allow made a model in settlement of a criminal offence in the criminal law of Indonesia in line with developments in the modern criminal law sanctions governing sanctions fines or compensation for victims.  Setting model jarimah-diyat can allow made a model in settlement of a criminal offence in the criminal law of Indonesia in line with developments in the modern criminal law sanctions governing sanctions fines or compensation for victims.